(untitled) (LEARNing Landscapes, 2021)
This article reports on collage as a pedagogical practice to support teacher candidate reflection. We outline a multi-step collage-based reflection workshop that was part of a required course on “Inquiries Into Learning.” The summative collage project was designed to help teacher candidates reflect on their vision of learning (hope) and their fears and doubts as beginning teachers. The process and product of their final integrated collage led students to interrogate how their hopes and fears mingle together in practice. Six teacher candidates share their series of collages and GIFs, along with their reflective personal statements. We conclude by highlighting lessons learned through collaging from the perspective of students.